Esophageal testing: What we have so far - de Bortoli, Nicola (World J Gastrointest Pathophysiol, 2016)
Gastroesophageal reflux disease (GERD) is a common disorder of the gastrointestinal tract. In the last few decades, new technologies have evolved and have been applied to the functional study of the esophagus, allowing for the improvement of our knowledge of the pathophysiology of GERD. High-resolution manometry (HRM) permits greater understanding of the function of the esophagogastric junction and the risks associated with hiatal hernia. Moreover, HRM has been found to be more reproducible and sensitive than conventional water-perfused manometry to detect the presence of transient lower esophageal sphincter relaxation. Esophageal 24-h pH-metry with or without combined impedance is usually performed in patients with negative endoscopy and reflux symptoms who have a poor response to anti-reflux medical therapy to assess esophageal acid exposure and symptom-reflux correlations. In particular, esophageal 24-h impedance and pH monitoring can detect acid and non-acid reflux events. EndoFLIP is a recent technique poorly applied in clinical practice, although it provides a large amount of information about the esophagogastric junction. In the coming years, laryngopharyngeal symptoms could be evaluated with up and coming non-invasive or minimally invasive techniques, such as pepsin detection in saliva or pharyngeal pH-metry. Future studies are required of these techniques to evaluate their diagnostic accuracy and usefulness, although the available data are promising.